Answer:
Explanation:
Long division:
Step 1:
We divide '3x²' by 'x' to get the first term of quotient.
⇒
Now, we multiply '3x' to
⇒
Now, we subtract
from the given numerator
. This gives,
Step 2:
We divide the first term of the above result by 'x' again to get the second term of the quotient.
⇒
Now, we multiply '-5' to
⇒
Now, we subtract
from the result obtained at the last of step 1
. This gives,
So, we stop division as we got a constant after subtraction. The constant is called the remainder and here the remainder is 0.
The quotient is our answer: